EFEKTIVITAS PEMANFAATAN ASSISTIVE TECHNOLOGY SEBAGAI ALAT EVALUASI HASIL BELAJAR MANDIRI BAGI SISWA TUNANETRA - Maulydiyah P; Zaidatul Fauzan, Riza; ZahraAprilia, Azh; Dwi Nugrah, Yovika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of assistive technology has created significant opportunities to improve educational accessibility for students with visual impairments, particularly in the assessment of learning outcomes. Technologies such as screen readers, refreshable Braille displays, optical character recognition (OCR) applications, and accessible digital assessment platforms enable students to participate in assessment activities more independently without relying on assistance from others. This article aims to analyse the effectiveness of assistive technology as a tool for assessing independent learning outcomes among students with visual impairments through a narrative literature review approach. The data were collected from national and international scholarly articles published between 2021 and 2025, retrieved from Google Scholar, Scopus, ERIC, SpringerLink, and Sage Journals. The selected articles were chosen based on their relevance, credibility, and alignment with the research objectives, and were analysed descriptively through data identification, reduction, synthesis, and interpretation. The findings indicate that the use of assistive technology improves the accessibility of assessment instruments, promotes students' independent learning, enhances the objectivity of assessment, and increases learners' confidence in participating in educational evaluation. However, its effectiveness is influenced by the availability of technological resources, teachers' competence in developing accessible assessment instruments, and students' digital literacy. Therefore, policy support, adequate technological infrastructure, and continuous professional development for teachers are essential to optimise the implementation of assistive technology in creating inclusive, fair, and learner-centred assessment practices for students with visual impairments